Students’ personal desire for excitement and teachers’ autonomy support in outdoor activity: Links to passion, intrinsic motivation, and effort - Waaler, Rune; Halvari, Hallgeir; Skjesol, Knut; Ulstad, Svein Olav (Journal for Research in Arts and Sports Education, 2022)
The purpose of the study was to test the role of the personal desire for excitement and its links to autonomy support, harmonious and obsessive passion, and longitudinal intrinsic motivation, and effort in students’ favorite outdoor activity. 675 students at Norwegian folk high schools [folkehøgskole] attending a one-year study of their favorite outdoor activity (for instance, hunting, fishing, mountain climbing, kiting, and sailing) completed a questionnaire package. The desire for excitement positively predicted perceived autonomy support and the two types of passion. Autonomy support positively predicted harmonious passion, which in turn was positively linked to change in intrinsic motivation, which again positively predicted change in effort. Length of experience moderated the link between desire for excitement and obsessive passion. Furthermore, participants with short experience in the activity, relative to those with long experience and males, reported a higher desire for excitement and a higher obsessive passion. Autonomy support from teachers is important for young adults pursuing activities giving experiences of excitement, speed, and risk. Teachers can be autonomy supportive by acknowledging students’ feelings and perspectives, encouraging self-initiation and exploration of new experiences, avoiding communicating pressuring expectations, and instead offering choice among different types of exercises and training methods that may help the participants to attain their personal goals. In such a social context, it is important that teachers encourage them to further explore and to improve their skills, as they understand their excitement-seeking personality. Autonomy support might help the students choose activities providing excitement arousal in a good way, instead of high-risk activities with negative consequences.